Determinants of Dividend Policy in Primary Consumer Goods Sector Companies on the Indonesia Stock Exchange - Putri Avikasari; Yul Tito Permadhy (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Dividend policy examines the issue that arises when a firm must decide whether to distribute profits as dividends or keep profits for future investment financing. This quantitative study targets to determine the effect of leverage, profitability, sales growth, and free cash flow on dividend policy. As the object of research, this study examines data from consumer non-cyclicals sector firms in the Indonesia stock exchange during the 2018-2020 period. Saturated sampling technique was used to select samples from non-cyclicals sector by obtaining 37 firms as research samples in the 2018-2020 period. The hypothesis was tested using the Panel Data Regression Analysis with Eviews 12 program and a significance level of 5%. The findings of the experiments found out that (1) leverage has an effect on dividend policy, (2) profitability has an effect on dividend policy, (3) sales growth has no effect on dividend policy, and (4) free cash flow has no effect on dividend policy.